KEBIJAKAN PERMINYAKAN NASIONAL: DARI KENDALI NEGARA MENUJU KAPITALISME PASAR - Ma?arif, Syamsul (Universitas Serang Raya, 2014)
This study aims to explain scarcity of domestic oil supply in Indonesia after more than one decade the Government implement liberalization over oil and gas sector under supervision of IMF. By using comparison to three periods of oil national policy, this study shows that significant change has happened in connection to role of the Government in economic. National economics, especially market of strategic commodity like petroleum sector, recently become more and more opened for foreign corporation to operate since the Government launched liberalization. Theoretically, the involvement of private sector especially foreign private in managing oil and gas sector expectedly can make security of domestic oil supply become more and more guaranted. However, the reality shows that Indonesia for last more one decade always experienced scarcity of domestic oil supply. In additional, domestic oil price tends to uncertain and instable as the result of fluctuation of global oil price. Thus, liberalization in contrary has made domestic energy surveilence become vulnerable to external shock. Scarcity of supply, uncertainty of price and instability, at the last rise as the result of policy failure